2016
DOI: 10.3109/15368378.2015.1075409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulsed electromagnetic field therapy on experimental pain: A double-blind, randomized study in healthy young adults

Abstract: Past studies have suggested that pulsed electromagnetic field (PEMF) therapy can decrease pain. To date, however, it remains difficult to determine if the analgesic effect observed in patients are attributable to a direct effect of PEMF on pain or to an indirect effect of PEMF on inflammation and healing. In the present study, we used an experimental pain paradigm to evaluate the direct effect of PEMF on pain intensity, pain unpleasantness and temporal summation of pain. Twenty-four healthy subjects (mean age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
1
7
2
1
Order By: Relevance
“…The result of this study disagreed with [44] who studied the effect of 50Hz magnetic field on sex hormones of adult female rats exposed to a 50Hz sinusoidal magnetic field at approximately 25 microT (0.25 Gauss) for 18 weeks. Serum level progesterone was measured before, after, and during the exposure.…”
Section: Discussioncontrasting
confidence: 99%
“…The result of this study disagreed with [44] who studied the effect of 50Hz magnetic field on sex hormones of adult female rats exposed to a 50Hz sinusoidal magnetic field at approximately 25 microT (0.25 Gauss) for 18 weeks. Serum level progesterone was measured before, after, and during the exposure.…”
Section: Discussioncontrasting
confidence: 99%
“…Confirmation of the above studies are the results of the studies of Pasek et al [17] and Beaulieu et al, [27] in which they showed a positive effect of a treatment with use of variable and static magnetic fields on the intensity of perceived pain of joints, also in patients suffering from OA of knee joints and joints of upper limbs.…”
Section: Discussionsupporting
confidence: 64%
“…Overview rTMS was first described by Baker et al in 1985 as a non-invasive, non-convulsive neuromodulatory therapy that utilizes alternating magnetic field to induce electromagnetic conduction in the electrical circuitry of the brain [13,32,33]. The user-generated magnetic field influences the electrically sensitive membrane potential of cortical neurons, which can affect the excitability or inhibition of specific neural circuits and may induce long-term potentiation or long-term depression, respectively.…”
Section: Repetitive Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…PEMF is another non-invasive neuromodulatory technique that uses electromagnetic fields to induce electrical induction to target specific tissues and has been explored as an analgesic technique [33]. Previous studies have found that PEMF enhances tissue recovery and repair via induction of Eddy currents, which may have an effect in gene expression such as the endogenous opioid pathways [54].…”
Section: Pulsed Electromagnetic Fieldmentioning
confidence: 99%
See 1 more Smart Citation